The relationship between psychological resilience and employability among higher vocational college students: the chain mediating effects of perceived social support and career decision-making self-efficacy - Xiong, Ye; Yu, Jijiang; Wu, Hewen (Frontiers in Psychology, 2026)
IntroductionThe global youth is facing challenges of large-scale job-seeking pressure and structural employment contradictions. Employability is a key factor in alleviating employment pressure. Grounded in the conservation of resources theory, this study aims to explore the relationship between psychological resilience and employability among higher vocational college students, with a specific focus on the chain mediating effects of perceived social support and career decision-making self-efficacy.MethodsA total of 1,709 students from five higher vocational colleges with industrial features in Jiangxi Province, China, were surveyed using the Psychological Resilience Scale, Perceived Social Support Scale, Career Decision-Making Self-Efficacy Scale, and Employability Scale. The relationships among these variables were tested using PROCESS plugin for SPSS version 27.0.ResultsThe results indicated that (1) there were significant positive correlations among all variables; (2) psychological resilience had a significant positive impact on employability; and (3) psychological resilience could affect employability through three indirect pathways, namely, the independent mediation of perceived social support and career decision-making self-efficacy, and their chain mediation.DiscussionIt is suggested that higher vocational colleges should integrate psychological resilience training into the curriculum, establish a multi-stakeholder collaborative support network, and implement experiential career guidance programs. This study provides an empirical support for improving employability among higher vocational college students.